FARMERS’ PERCEPTIONS ON EXPANSION OF A NEW TECHNOLOGY: THE CASE OF COCONUT-BASED INTERCROPPING IN SRI LANKA - M.T.N. Fernando; M.E. Daw; I.E. Edwards (International Coconut Community, 2003)
Monocropping, the widely practiced traditional coconut cultivation system in Sri Lanka, utilizes bio-physical resources sub optimally, generating low returns to growers than its potential under an intensive cultivation alternative, coconut-based intercropping (CBI). Despite concerted efforts of successive governments, the adoption of CBI systems by farmers is low. This study investigates the farmers' perceptions of CBI on the premise that the understanding of farmers’ perceptions of a new technology is important to identify the causes for the low adoption of that technology. Data were gathered by a field survey of 113 and 37 intercroppers and monocroppers respectively, in three main coconut-growing districts, namely Kurunegala, Gampaha and Puttalam, using a structured questionnaire supplemented with open-ended questions, through a single visit. Percentage analysis supplemented with a simple scoring device was employed to analyze the farmer's perceptions of CBI. Intercroppers objectives of intercropping, the constraints they face in expanding intercropping, reasons for non-adoption of CBI by present monocroppers and the suggestions of present intercroppers to further expand the CBI, all in the order of importance, are presented.